2012
DOI: 10.1088/0264-9381/29/9/095004
|View full text |Cite
|
Sign up to set email alerts
|

Fully explorable horned particles hiding charge

Abstract: The charge-hiding effect by a horned particle, which was studied for the case where gravity/gauge-field system is self-consistently interacting with a charged lightlike brane (LLB) as a matter source, is now studied for the case of a time like brane. From the demand that no surfaces of infinite coordinate time redshift (horizons) appear in the problem we are lead now to a completly explorable horned particle space for traveller that goes through the horned particle (as was the case for the LLB) but now also in… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 73 publications
0
10
0
Order By: Relevance
“…, resulting from the corrections to the Maxwell Lagrangian in (1). The appareance of a cosmological constant term r 2 /6r 2 g in ( 48) is a similar effect to that found in [17]. In (48) we have kept the minimum number of terms containing both ultraviolet corrections due to the gravitational Lagrangian, which manifest the existence of a wormhole structure, and infrared corrections coming from the matter sector, which are responsible for the asymptotically de Sitter behavior.…”
Section: De Sitter Behavior When X ≫mentioning
confidence: 95%
See 1 more Smart Citation
“…, resulting from the corrections to the Maxwell Lagrangian in (1). The appareance of a cosmological constant term r 2 /6r 2 g in ( 48) is a similar effect to that found in [17]. In (48) we have kept the minimum number of terms containing both ultraviolet corrections due to the gravitational Lagrangian, which manifest the existence of a wormhole structure, and infrared corrections coming from the matter sector, which are responsible for the asymptotically de Sitter behavior.…”
Section: De Sitter Behavior When X ≫mentioning
confidence: 95%
“…In this work we present wormhole-type solutions with a dynamically generated cosmological constant in the quadratic Palatini extension of GR studied in [7,8,9]. The matter sector of our theory, responsible for the dynamical generation of a cosmological constant [17] (see also [18]), will be described by a nonlinear theory of electrodynamics given by the Lagrangian density…”
Section: Introductionmentioning
confidence: 99%
“…Naturally this takes us away from classical physics into the realm of gravity coupled QCD. Let us add that hiding of charge by geometrical structures has been considered before for example in [28]. Therein with cited references, it has been shown that non-linear contributions (see for instance [29]) in an effective theory beyond standard Einstein-Maxwell plays crucial roles.…”
Section: Discussionmentioning
confidence: 95%
“…In Ref. [23] we have considered a theory describing confinement, in flat spacetime, through a non-linear Maxwell term in the form of…”
Section: Summary and Future Workmentioning
confidence: 99%